KORESPONDENSI BISNIS DALAM PERDAGANGAN INTERNASIONAL: BAGAIMANA PERANNYA TERHADAP KINERJA FREIGHT FORWARDER? HOW DOES IT IMPACT FREIGHT FORWARDERS' PERFORMANCE? - Dedi Febrianto; Fajria Fatmasari (Universitas Djuanda Bogor, 2022)
Business correspondence in the form of e-mail has an important role for freight forwarders to support their duties as intermediaries between exporters and importers. Mastering the style, format, and important parts of an e-mail is not an easy job, especially if it is written in English so that it becomes a challenge for freight forwarders. This study tries to investigate the obstacles and challenges faced by freight forwarding companies in Indonesia in conducting business correspondence in English, as well as analyze the role of business correspondence towards working performance of freight forwarders. This study involved five freight forwarding companies located in Jakarta. Data were collected through literature study and interviews with staff who handle correspondence. The results show that the style of e-mail communication made by freight forwarding companies tends to be informal with a lot of use of abbreviations and concise forms of e-mail. In addition, there are several obstacles in conducting correspondence, namely the lack of knowledge about the components that make up an e-mail, lack of English language skills, lack of knowledge about e-mail writing style, and misinterpretation. The obstacles impacted export-import activities in the form of delays in transaction processing, customer complaints and financial losses. Employees who deal with correspondence should be given intensive business correspondence training in order to understand in detail the structure, writing style, and patterns of business correspondence commonly used in the international business world. In addition, it is necessary to improve English language skills for the employees by providing English language training, especially related to writing and grammar.